An Important Problem: Posttransplant Focal Segmental Glomerulosclerosis Recurrence and Plasmapheresis - KAZANCIOĞLU, RÜMEYZA; EMRE, Turker; Kazancioglu, RÜMEYZA; DOGAN, Huseyin; Caliskan, Yasar Kerem; KAHVECIOGLU, Serdar; Turkmen, Aydin (My University, 2015)
OBJECTIVE : Focal segmental glomerulosclerosis (FSGS) as a primary glomerular disease are refractory to therapy and progress to End stage renal disease. (ESRD). After transplantation, the major problems are recurrence of the disease and its treatment. In this study, We investigated FSGS recurrence.